Role of Complexing Agent in Chemical Bath Deposition of Thin Films: A Review - Ho, Soon Min (American-Eurasian Network for Scientific Information, 2015)
Background: An economical and simple chemical bath deposition technique for depositing various types of thin films has been reported by many researchers. Objective: In this work, the main objective is to investigate the role of complexing agent in the chemical bath deposited thin films. Results: As we know, complexing agent is one of the crucial chemical additives in preparation of thin films. Therefore, the influence of the complexing agent on the structural, optical, surface morphological and electrical properties of films was highlighted. The obtained films were characterized using various tools such as SEM, AFM, XRD, EDX and UV-Visible spectrophotometer. Conclusion: The experimental findings indicated that the films prepared in the presence of complexing agent were good quality thin films.